Uncemented versus cemented arthroplasty after metal-on-metal total hip replacement in patients with femoral neck fractures: a retrospective study. Issue 5 (May 2021) - Liu, Wenlu; Lin, Huanyi; Zeng, Xianshang; Chen, Meiji; Tang, Weiwei; Zhou, Ting; Yu, Weiguang; Liu, Qilong; Xu, Guixing
Objective: To compare the clinical outcomes of primary metal-on-metal total hip replacement (MoM-TR) converted to uncemented total hip replacement (UTR) or cemented total hip replacement (CTR) in patients with femoral neck fractures (AO/OTA: 31B/C). Methods: Patient data of 234 UTR or CTR revisions after primary MoM-TR failure from March 2007 to January 2018 were retrospectively identified. Clinical outcomes, including the Harris hip score (HHS) and key orthopaedic complications, were collected at 3, 6, and 12 months following conversion and every 12 months thereafter. Results: The mean follow-up was 84.12 (67–100) months for UTR and 84.23 (66–101) months for CTR. At the last follow-up, the HHS was better in the CTR- than UTR-treated patients. Noteworthy dissimilarities were correspondingly detected in the key orthopaedic complication rates (16.1% for CTR vs. 47.4% for UTR). Statistically significant differences in specific orthopaedic complications were also detected in the re-revision rate (10.3% for UTR vs. 2.5% for CTR), prosthesis loosening rate (16.3% for UTR vs. 5.9% for CTR), and periprosthetic fracture rate (12.0% for UTR vs. 4.2% for CTR). Conclusion: In the setting of revision of failed primary MoM-TR, CTR may demonstrate advantages over UTR in improving functional outcomes and reducing key orthopaedic complications.